Clinical relevance of different handgrip strength indexes and metabolic syndrome in Chinese community-dwelling elderly individuals. (March 2020) - Song, Peiyu; Zhang, Yuanyuan; Wang, Yue; Han, Peipei; Fu, Liyuan; Chen, Xiaoyu; Yu, Hairui; Hou, Lin; Yu, Xing; Wang, Lu; Yang, Fengying; Guo, Qi
Highlights: Relative handgrip strength predicts MetS superior to absolute handgrip strength. The overall prevalence of MetS is 38.4 % in this study. HS/body fat mass appears to be the index best associated with MetS. The cut-off value of HS/body fat mass to detect MetS is 1.92 in men and 1.25 in women. Abstract: Purpose: Currently there is no consensus on the correlation between metabolic syndrome (MetS) and muscle strength. The objective of this study was to examine the associations between MetS and its components and different handgrip strength (HS) indexes among Chinese community-dwelling elderly individuals. In addition, we hoped to find an optimal cutoff point for the index most relevant to MetS. Methods: Data were obtained from 909 participants aged ≥ 60 years (385 men, average age, 68.0 ± 5.9 y). We used the International Diabetes Federation metabolic syndrome guidelines to define MetS. General data of all participants were collected through questionnaires and anthropometric data were measured. At the same time, blood samples were collected. Results: The prevalence of MetS was 26.8 % in men and 46.9 % in women. In all HS indexes, HS/body fat mass was most strongly correlated with MetS, and the areas under the receiver-operating characteristic curve were 0.723 (95 % confidence interval [CI] = 0.669-0.776) in men and 0.619 (95 % CI = 0.571-0.667) in women, and the optimal cutoffs were 1.92 in men and 1.25 in women. The adjusted odds ratios (ORs) of MetS for low HS/body fat mass were 5.38 (95 % CI = 3.03–9.56, p < 0.001) in men and 2.39 (95 % CI = 1.56–3.64, p < 0.001) in women. Conclusions: HS/body fat mass appears to be the index best associated with MetS and its components, and in men it is more relevant than in women.